2018
DOI: 10.17221/328/2017-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical changes in mango fruit in response to Alternaria alternata infection

Abstract: Changes in mango fruit quality, malondialdehyde content, and enzymatic activities in response to pathogen Alternaria alternata infection were studied. A. alternata significantly affected the appearance of mango fruit at 5 and 7 days after treatment (DAT). The quality of pathogen-infected fruit first showed a significant decrease in titratable acidity and vitamin C content and a significant increase in pH since 3 DAT. The malondialdehyde content was higher than that in the untreated controls at 3 and 7 DAT. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 25 publications
3
3
0
Order By: Relevance
“…33 The activity of CAT was lower in inoculated fruits of Una and Kurtovska kapia than in control fruits. This is consistent with the results of Li et al 34 who found decrease in CAT activity in mango fruits infected by A. alternata. However, water-injected fruits of Kurtovska kapia showed the highest CAT activity.…”
Section: Accepted Manuscriptsupporting
confidence: 93%
See 1 more Smart Citation
“…33 The activity of CAT was lower in inoculated fruits of Una and Kurtovska kapia than in control fruits. This is consistent with the results of Li et al 34 who found decrease in CAT activity in mango fruits infected by A. alternata. However, water-injected fruits of Kurtovska kapia showed the highest CAT activity.…”
Section: Accepted Manuscriptsupporting
confidence: 93%
“…4). Obtained results are in agreement with those of Li et al 34 who reported an increase in MDA concentration in mango fruits infected by A. alternata. To observe the relationship among examined bioactive compounds, enzyme activity, genotypes and wounding and infection stress, principal component analysis (PCA) (Fig.…”
Section: Accepted Manuscriptsupporting
confidence: 93%
“…SOD is a metalloenzyme that catalyzes the dismutation of superoxide anion to oxygen and H2O2 thus, protecting plant tissues from oxidation of lipids and DNA damages (Badejo et al, 2016). It is the first defense mechanism that converts free oxygen radicals O2 to H2O2 to scavenge other free radicals (Li et al, 2018). The observed increase as storage period increased is in conjunction with the findings of Razavi et al (2018) in stored peach fruits at 1 o C for 2-4 weeks.…”
Section: Antioxidant Enzymes Activities Of African Star Apple Juice D...supporting
confidence: 75%
“…Possible strategies to limit Alternaria infection include: (1) obtaining resistant cultivars in breeding programs. In this regard, the studies conducted so far point to the plant’s ability to increase phenolic compounds and its antioxidant metabolism as good traits to select for [ 33 , 34 , 35 ]; (2) selecting adequate cultivation and field management techniques in order to reduce fungi invasion [ 14 , 36 ]. Cultivation practices, such as maintaining a healthy field and crop vigor and removing infected plant debris, are helpful in controlling fungi invasion, but are not always sufficient; (3) improving postharvest handling, since vegetables can also be contaminated by A. alternata mycotoxins during this period [ 37 ].…”
Section: Introductionmentioning
confidence: 99%